2021
DOI: 10.1002/uog.23639
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between viral load, infection‐to‐delivery interval and mother‐to‐child transfer of anti‐SARS‐CoV‐2 antibodies

Abstract: What are the novel findings of this work?In pregnant women who have recovered from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, anti-SARS-CoV-2 immunoglobulin G (IgG) concentrations at delivery increased with increasing viral load during infection and decreased with increasing infection-to-delivery interval. The median transplacental transfer ratio of IgG was 1.3 and it decreased with increasing viral load during infection. What are the clinical implications of this work?Even though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 5 publications
2
15
1
1
Order By: Relevance
“…[7][8][9][10] We previously demonstrated that 75% of pregnant women with laboratory-confirmed SARS-CoV-2 infection were seropositive at delivery. 11 In addition to the strict control measures mentioned above, the low seroprevalence recorded in our study might have been related to undetectable antibody levels at the time of specimen collection-the timing of blood sample collection might not have been compatible with antibody detection. However, this is unlikely to have affected the findings among the large number of pregnant women in this study.…”
Section: Discussionmentioning
confidence: 70%
“…[7][8][9][10] We previously demonstrated that 75% of pregnant women with laboratory-confirmed SARS-CoV-2 infection were seropositive at delivery. 11 In addition to the strict control measures mentioned above, the low seroprevalence recorded in our study might have been related to undetectable antibody levels at the time of specimen collection-the timing of blood sample collection might not have been compatible with antibody detection. However, this is unlikely to have affected the findings among the large number of pregnant women in this study.…”
Section: Discussionmentioning
confidence: 70%
“…The qualitative reporting of SARS-CoV-2 RT-PCR testing as positive or negative is sufficient for diagnosis but it is supplemented by the Ct value, a semi-quantitative value [7] that refers to the number of cycles needed to amplify the viral RNA to a detectable level [12] . This Ct value, together with the time of onset of symptoms will help guide infection control, public health, and occupational health decisions [5] which are essential in the clinical management of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Robust humoral response elicited by SARS-CoV-2 infection and vaccination, and efficient IgG transfer in pregnancy have been widely reported (10,(17)(18)(19)(20)(21). Previous studies indicate that the receptor-binding domain (RBD) of the SARS-CoV-2 Spike protein contains multiple conformational neutralizing epitopes (22).…”
Section: Abstract (200 Words)mentioning
confidence: 99%